Deformation behaviour of lath martensite in multi-phase steels. (1st January 2016) - Maresca, F.; Kouznetsova, V.G.; Geers, M.G.D.
Graphical abstract: Abstract: This paper analyses the role of interlath retained austenite films within the martensite islands on the local strain partitioning and overall mechanical response of dual phase steels. A crystal plasticity-based modelling approach is thereby adopted. It is shown that the presence of a negligible (< 2 % ) volume fraction of interlath austenite amplifies the strain heterogeneity in both the martensite islands and the surrounding ferrite matrix. This qualitatively matches experimental observations from literature, showing a highly anisotropic, orientation dependent local mechanical response of martensite. The results emphasise the potential key role played by interlath austenite films in microstructures involving lath martensite.